The spatial distribution pattern of coffee shops in Kuta Alam District, Banda Aceh - Yusuf, Myna Agustina; Nurnazirah, Nurnazirah; Arafah, Yunita (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The Aceh Province, recognized as one of the world's finest coffee producers, is also known as the "Land of 1001 Coffee Shops," reflecting its deeply rooted coffee-drinking culture. In Banda Aceh, the growth of coffee shops has increasingly concentrated in the city center, driven by a shift in young people's preferences for public social spaces. Coffee shop locations play a dual role as commercial facilities and public spaces, emphasizing their significance in connecting activities within specific zoning and spatial functions. This study aimed to identify the distribution pattern of coffee shop locations in the Kuta Alam subdistrict, designated in Banda Aceh’s Detailed Spatial Plan for trade, services, residential, and public service zones. Data collection involved identifying 109 coffee shop locations. The analysis employed quantitative and spatial methods. The findings revealed that the spatial distribution of coffee shops in Kuta Alam predominantly occurs along local roads, with clustering along secondary arterial roads and the least presence on primary arterial roads. Most coffee shops are located near residential areas, regardless of road classifications. All coffee shops in Kuta Alam exhibit clustered spatial distribution (average nearest neighbor index below 1) clustering occurs in areas like Bandar Baru and Peunayong and along roads such as Syiah Kuala.